Mastering Windows Server 2019 : the Complete Guide for IT Professionals to Install and Manage Windows Server 2019 and Deploy New Capabilities, 2nd Edition. - Krause, Jordan (Packt Publishing Ltd, 2019)
Windows Server 2019 is the server operating system developed by Microsoft as part of the Windows NT family of operating systems. With Windows Server 2019, Microsoft has gotten us thinking outside of the box for what it means to be a system administration, and comes with some interesting new capabilities. Mastering Windows Server 2019 covers ...